Double-layer copper foil and preparation method and application thereof

By applying an antioxidant coating composed of metal and organic coatings on the copper foil, the problem of oxidation of copper foil during high-temperature pressing is solved, maintaining electrical conductivity and improving the performance of printed circuit boards, while achieving efficient separation of copper foil and improving production efficiency.

CN119676940APending Publication Date: 2025-03-21JIUJIANG TELFORD ELECTRONICS MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411576746.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Traditional copper foils are prone to oxidation during high-temperature pressing, resulting in reduced conductivity, affecting the performance of printed circuit boards, and at the same time, the efficiency of the stacking process is low.

Method used

An antioxidant coating consisting of metal coatings and organic coatings is used to prevent the oxidation of the copper foil and to isolate the two layers of copper foil at high temperatures to enable separation, thereby improving production efficiency.

Benefits of technology

It effectively prevents copper foil oxidation, maintains conductivity, improves the performance of printed circuit boards, and achieves efficient production through interlayer separation, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119676940A_ABST
    Figure CN119676940A_ABST
Patent Text Reader

Abstract

The invention relates to a double-layer copper foil as well as a preparation method and application thereof. The double-layer copper foil comprises a first copper layer, an anti-oxidation coating and a second copper layer, the anti-oxidation coating is composed of a metal coating and an organic coating. The anti-oxidation coating adopted by the invention can effectively prevent the copper foil from being oxidized when the copper foil and the prepreg are pressed, so that the conductivity of the copper foil is ensured, and the performance of the printed circuit board is improved; meanwhile, the coating can effectively isolate two layers of copper foils at high temperature, so that the copper foils can be separated from layers, two copper-clad plates with the copper foils can be obtained in one pressing unit, the production efficiency is improved, and the copper-clad plate has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material processing, and in particular relates to a double-layer copper foil and a preparation method and application thereof. Background Art

[0002] In the field of metal material processing, copper foil is a commonly used thin substrate. Due to its good electrical and thermal conductivity, it is widely used in the field of electronic materials, especially in the process of manufacturing printed circuit boards (PCBs), where copper foil plays a vital role. The traditional electrolytic copper foil for electronic circuits is a single-layer copper structure. During the downstream pressing process with the prepreg, it is stacked and pressed with the prepreg to embed the copper foil in the prepreg, thereby obtaining a plate with copper foil, namely a copper-clad laminate. The copper-clad laminate is then subjected to a series of steps such as lamination, exposure, development, and etching to finally obtain a printed circuit board.

[0003] Since copper foil is prone to oxidation during high-temperature lamination, especially during lamination with prepreg, an oxide layer is easily formed on the non-laminated surface. The formation of the oxide layer will reduce the conductivity of the copper foil and affect the performance of the printed circuit board. At the same time, the existing technology requires lamination before lamination of the copper foil and the prepreg, specifically steel plate-backing foil-copper foil-prepreg-copper foil-backing foil-steel plate as a unit, and one unit produces a copper clad laminate. In addition, the alignment of each layer of material in the lamination process must also be considered during the lamination process, resulting in low overall efficiency. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a double-layer copper foil and a preparation method and application thereof. The anti-oxidation coating used can effectively prevent the copper foil from being oxidized when it is pressed with a prepreg, thereby ensuring the conductivity of the copper foil and improving the performance of the printed circuit board; at the same time, the coating can effectively isolate the two layers of copper foil at high temperature, so that the copper foil can be separated from the layers, so that two copper-clad boards with copper foil can be obtained in one pressing unit, thereby improving production efficiency and having good application prospects.

[0005] The invention provides a double-layer copper foil, comprising a first copper layer, an anti-oxidation coating and a second copper layer; the anti-oxidation coating consists of a metal coating and an organic coating.

[0006] Preferably, the metal coating is selected from one or more of aluminum, titanium, chromium, niobium and nickel. These metals have good anti-oxidation properties and can protect the copper foil from oxidation under high temperature (250° C.). At the same time, the metal coating will not increase the thickness of the printed circuit board, which is conducive to the miniaturization and lightweight of the printed circuit board.

[0007] Preferably, the metal coating electrolyte concentration used in the metal coating is 0.1-1.5 g / L, and the electrolyte temperature is 40-55°C.

[0008] Preferably, the organic coating is selected from one or more coatings consisting of selenium-containing organic compounds, vinyl organic compounds and amino organic compounds.

[0009] Preferably, the organic coating solution used in the organic coating has a concentration of 1-5 g / L.

[0010] Furthermore, after the anti-oxidation coating is attached, a coating homogenization treatment is performed to ensure that the surface properties of the coating are isotropic.

[0011] Preferably, the homogenization treatment temperature is 50-250° C. and the time is 2-15 h.

[0012] Preferably, the thickness of the first copper layer and the second copper layer is 1-40 μm.

[0013] The present invention also provides a method for preparing a double-layer copper foil, comprising the following steps:

[0014] A metal coating is electroplated on the first copper layer using an electrolytic process, and then an organic coating is applied to the outer surface of the metal coating using a coating process to form a uniform and dense anti-oxidation coating, and the coating is homogenized; finally, a second copper layer is prepared on the surface of the anti-oxidation coating by electrodeposition to obtain a double-layer copper foil.

[0015] The first copper layer and the second copper layer are prepared by conventional processes without special requirements.

[0016] Furthermore, the method also includes roughening the outer side of the obtained double-layer copper foil.

[0017] Furthermore, after the roughening treatment is completed, the surface is subjected to an anti-oxidation treatment.

[0018] There are no special requirements for the process parameters of the roughening treatment and anti-oxidation treatment.

[0019] The invention also provides an application of a double-layer copper foil in preparing a copper-clad laminate.

[0020] Preferably, the stacking structure of the copper clad laminate is steel plate-backing foil-copper foil-prepreg-double-layer copper foil-prepreg-copper foil-backing foil-steel plate.

[0021] Beneficial Effects

[0022] (1) The anti-oxidation coating used in the present invention can effectively prevent the copper foil from being oxidized when being pressed with the prepreg, thereby ensuring the conductivity of the copper foil and improving the performance of the printed circuit board; at the same time, the coating can effectively isolate the two layers of copper foil at high temperature, so that the copper foil can be separated from the layers, so that two copper-clad boards with copper foil can be obtained in one pressing unit, thereby improving production efficiency and having good application prospects.

[0023] (2) The anti-oxidation coating of the present invention is achieved by a physical isolation method, that is, the coating is located between two layers of copper foil, which does not increase the thickness of the printed circuit board, and thus does not affect the miniaturization and lightweight of the printed circuit board. This is significantly better than the macroscopic physical isolation method in the prior art, and solves the defect of the prior art that the thickness of the printed circuit board is increased.

[0024] (3) The anti-oxidation coating of the present invention not only has an anti-oxidation function, but also has good adhesion and can be firmly attached to the surface of the copper foil, thereby improving the durability and reliability of the coating. At the same time, the coating can be prepared by electroplating or other surface treatment methods, with simple process, low cost, and easy large-scale production.

[0025] (4) The double-layer copper foil of the present invention can be homogenized without increasing the thickness of the printed circuit board. It can prevent oxidation of a large area of ​​copper foil and ensure that the first copper layer and the second copper layer do not adhere to each other. This is obviously better than the existing technology, comprehensively solves the problems of the existing technology in preventing oxidation of copper foil and production efficiency, and has high practical value. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the structure of the double-layer copper foil of the present invention;

[0027] Figure 2 It is a schematic structural diagram of a copper-clad laminate using a double-layer copper foil of the present invention;

[0028] 1 is the first copper layer; 2 is the anti-oxidation coating; 3 is the second copper layer; 4 is the double-layer copper foil; 5 is the prepreg; 6 is the outer copper foil. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0030] Example 1

[0031] Figure 1 The schematic diagram of the structure of the double-layer copper foil of this embodiment is shown in FIG. The overall manufacturing process is the preparation of the first copper layer, the preparation of the anti-oxidation coating, the preparation of the second copper layer, and the surface treatment. The detailed preparation process of the double-layer copper foil of this embodiment will be described below according to the production sequence.

[0032] S1. First, the first copper layer is prepared by electrolysis equipment. The electrolyte is a copper sulfate solution containing sulfuric acid with a concentration of 110 g / L and Cu 2+ The ion concentration is 97g / L H 2 SO 4 ·5H 2 O. In an electrolyte at 54°C, at 40A / dm 2 Electrolysis was performed for 45 seconds at a current density of 1.50 Å to obtain a first copper layer with a thickness of 18 μm.

[0033] S2. After the first copper layer is prepared, sulfuric acid is used as a treatment liquid to spray and soak both sides of the copper foil for 20 seconds to remove surface impurities or oxide film. The treatment liquid is sulfuric acid with a concentration of 85g / L and a treatment liquid temperature of 40°C.

[0034] S3. After removing impurities or oxide film on the surface of the first copper layer, the first copper layer is brought into a metal coating electrolyte to prepare a metal coating. The chromic anhydride concentration in the metal coating electrolyte is 0.5 g / L, and the electrolyte temperature is 45°C.

[0035] S4. After the metal coating electrodeposition is completed, the copper foil is immersed in an organic coating solution for 20 seconds. The organic coating solution contains a polyethylene glycol ether aqueous solution with a concentration of 3 g / L.

[0036] S5. To ensure the uniformity of the anti-oxidation coating, the copper foil is placed in a homogenizing device for surface homogenization treatment. The treatment temperature of this step is 200° C. and the treatment time is 2 hours.

[0037] S6. After the metal coating and the organic coating are homogenized, electrolysis is started on the organic coating side to form a second copper layer. The electrolysis method of the second copper layer is the same as that of the first copper layer. During electrolysis, the sulfuric acid concentration in the electrolyte is 110g / L. 2+ The ion concentration is 97g / L H 2 SO 4 ·5H 2 O. In an electrolyte at 54°C, at 40A / dm 2 Electrolysis was carried out for 45 seconds at a current density of , to obtain a second copper layer with a thickness of 18 μm, i.e., a double-layer copper foil.

[0038] S7. After the second copper layer is electrolyzed, the outer side of the double-layer copper foil is roughened to ensure the copper foil adheres firmly after lamination. Fine copper particles are first formed on the surface, and then the copper particles are fixed on the outer surface of the copper foil by solidification electroplating.

[0039] The concentration of sulfuric acid used for fine copper particle electroplating is 110g / L, Cu 2+ The copper sulfate solution with an ion concentration of 20g / L. The double-layer copper foil is introduced into the copper sulfate electrolyte at 14A / dm 2The copper foil was electroplated at an average current density of 12s to obtain a double-layer copper foil with rough surfaces. 2+ Solidification electroplating was carried out in a copper sulfate solution with an ion concentration of 50g / L and an electroplating current density of 12A / dm 2 , electroplating time 12s.

[0040] S8. After the roughening process, in order to ensure the surface performance of the copper foil in long-term storage or harsh environment, the surface needs to be treated with anti-oxidation. The anti-oxidation treatment layer is a cobalt-plated layer and a zinc-plated layer. The sulfuric acid concentration of the cobalt-plated layer electrolyte is 75g / L, the cobalt concentration is 10g / L, the electrolysis temperature is 40℃, and the current density is 12A / dm 2 , electroplating time 10s; zinc coating sulfuric acid concentration 85g / , zinc concentration 18g / L, electrolysis temperature 45℃, current density 10A / dm 2 After the above two times of non-copper metal electroplating, an anti-oxidation layer can be attached to the surface of the double-layer copper foil, and finally the electrolyte or water stains on the surface of the double-layer copper foil are removed by spraying water washing and oven drying.

[0041] The structure of a laminate unit in the copper clad laminate prepared with the double-layer copper foil is steel plate-backing foil-copper foil-prepreg-double-layer copper foil-prepreg-copper foil-backing foil-steel plate, and its main structure is steel plate-copper foil-prepreg-double-layer copper foil-prepreg-copper foil-steel plate. Figure 2 The unit was taken out after being heated at 250°C for 1 hour, and the two cured prepregs were separated from the anti-oxidation coating interface of the double-layer copper foil by applying external forces in opposite directions, and two copper-clad laminates with 18μm copper foil attached to both sides were obtained.

[0042] The copper-clad plate prepared with the double-layer copper foil can obtain a printed circuit board made with the double-layer copper foil after the steps of coating a photosensitive film, exposing, developing, copper plating, film removal, etching, surface treatment and cutting.

[0043] The copper foil laminated with double copper foil was tested. After heating at 250℃ for 1 hour, the two cured prepregs could be completely separated. After the copper clad laminate prepared by pressing with epoxy resin as the substrate was separated, the metal content of the intermediate anti-oxidation coating was extremely poor at 0.7mg / m 2 The two copper layers were thickened to 35μm and the peel strength was tested. The peel strength of the first copper layer was 1.23N / mm, and the extreme difference in peel strength was 0.11N / mm. The peel strength of the first copper layer was 1.05N / mm, and the extreme difference in peel strength was 0.08N / mm.

[0044] Example 2

[0045] The difference between this embodiment and embodiment 1 is that (1) the thickness of the first copper layer is adjusted to 35 μm; (2) the thickness of the second copper layer is adjusted to 1.5 μm. (3) the type of metal coating is adjusted, and nickel and chromium are selected as the metal coating materials (the concentrations of nickel and chromium are 0.8 g / L and 1.5 g / L respectively); (4) the type of organic coating is adjusted to L-seleno-methylselenocysteine. (5) the homogenization step is adjusted, the temperature is changed to 70°C, and the time is 0.5 h.

[0046] The copper foil laminated with double copper foil was tested. After heating at 250℃ for 1 hour, the two cured prepregs could be completely separated. After the copper clad laminate prepared by pressing with epoxy resin as the substrate was separated, the metal content of the intermediate anti-oxidation coating was extremely poor at 0.5mg / m 2 The two copper layers were thickened to 35μm and the peel strength was tested. The peel strength of the first copper layer was 1.31N / mm, and the extreme difference in peel strength was 0.08N / mm. The peel strength of the first copper layer was 1.22N / mm, and the extreme difference in peel strength was 0.15N / mm.

[0047] Example 3

[0048] The difference between this embodiment and embodiment 1 is that (1) the thickness of the first copper layer is adjusted to 8 μm; (2) the thickness of the second copper layer is adjusted to 35 μm. (3) the type of metal coating is adjusted, and aluminum and niobium are selected as the metal coating materials (the concentrations of aluminum and niobium are 1.5 g / L and 0.4 g / L respectively); (4) the type of organic coating is adjusted to 4-(phenylamino)-triphenylamine. (5) the homogenization step is adjusted, the temperature is changed to 120°C, and the time is 3 hours.

[0049] The copper foil laminated with double copper foil was tested. After heating at 250℃ for 1 hour, the two cured prepregs could be completely separated. After the copper clad laminate prepared by pressing with epoxy resin as the substrate was separated, the metal content of the intermediate anti-oxidation coating was extremely poor at 0.8mg / m 2 The two copper layers were thickened to 35μm and the peel strength was tested. The peel strength of the first copper layer was 1.07N / mm, and the extreme difference of peel strength was 0.9N / mm. The peel strength of the first copper layer was 1.25N / mm, and the extreme difference of peel strength was 0.11N / mm.

[0050] Example 4

[0051] The difference between this embodiment and embodiment 1 is that (1) the metal type of the metal coating is adjusted, and nickel and titanium are selected as the metal coating materials (the concentrations of nickel and titanium are 0.8 g / L and 0.2 g / L respectively); (2) the type of the organic coating is adjusted, and it is changed to 5-aminolevulinic acid hydrochloride. (3) The homogenization step is adjusted, and the temperature is changed to 50° C. and the time is 12 hours.

[0052] The copper foil laminated with double copper foil was tested. After heating at 250℃ for 1 hour, the two cured prepregs could be completely separated. After the copper clad laminate prepared by pressing with epoxy resin as the substrate was separated, the metal content of the intermediate anti-oxidation coating was extremely poor at 0.3mg / m 2 The two copper layers were thickened to 35μm and the peel strength was tested. The peel strength of the first copper layer was 1.14N / mm, and the extreme difference of peel strength was 0.10N / mm. The peel strength of the first copper layer was 1.3N / mm, and the extreme difference of peel strength was 0.09N / mm.

[0053] Comparative Example 1

[0054] The difference between this comparative example and Example 1 is that (1) the metal electroplating process in the anti-oxidation coating is eliminated, and only the organic coating is retained.

[0055] When testing the copper foil laminated with double copper foil, after heating at 250℃ for 1 hour, the two cured prepregs could not be separated and two completed copper clad laminates could not be formed. The metal content was extremely poor and could not be tested.

[0056] Comparative Example 2

[0057] The difference between this comparative example and Example 1 is that (1) the organic coating in the anti-oxidation coating is eliminated and only the metal coating is retained.

[0058] When testing the copper foil laminated with double copper foil, after heating at 250℃ for 1 hour, the two cured prepregs can be partially separated, but the rest cannot be separated, and two completed copper clad laminates cannot be formed. The metal content is extremely poor and cannot be tested.

[0059] Comparative Example 3

[0060] The difference between this comparative example and Example 1 is that (1) the homogenization step is adjusted, the temperature is changed to 40° C., and the time is 12 h.

[0061] When testing the double-layer copper foil laminated copper foil, after heating at 250°C for 1 hour, the two cured semi-cured sheets were partially separable, but the rest were inseparable, and two completed copper-clad laminates could not be formed. The metal content was extremely poor and could not be tested.

[0062] Comparative Example 4

[0063] The difference between this comparative example and Example 1 is that (1) the homogenization step is adjusted, the temperature is changed to 250° C., and the time is 1 h.

[0064] When testing the copper foil laminated with double copper foil, after heating at 250℃ for 1 hour, the two cured prepregs can be partially separated, but the rest cannot be separated, and two completed copper clad laminates cannot be formed. The metal content is extremely poor and cannot be tested.

Claims

1. A double-layer copper foil, characterized in that: The invention comprises a first copper layer, an anti-oxidation coating and a second copper layer; the anti-oxidation coating is composed of a metal coating and an organic coating.

2. The double-layer copper foil according to claim 1, characterized in that: The metal coating is selected from one or more of aluminum, titanium, chromium, niobium and nickel.

3. The double-layer copper foil according to claim 1, characterized in that: The organic coating is selected from one or more coatings composed of selenium-containing organic compounds, vinyl organic compounds and amino-containing organic compounds.

4. The double-layer copper foil according to claim 1, characterized in that: After the anti-oxidation coating is attached, a coating homogenization treatment is performed.

5. A method for preparing a double-layer copper foil according to any one of claims 1 to 4, comprising the following steps: A metal coating is electroplated on the first copper layer using an electrolytic process, and then an organic coating is applied to the outer surface of the metal coating using a coating process to form a uniform and dense anti-oxidation coating, and the coating is homogenized; finally, a second copper layer is prepared on the surface of the anti-oxidation coating by electrodeposition to obtain a double-layer copper foil.

6. The preparation method according to claim 5, characterized in that: The method also includes roughening the outer side of the obtained double-layer copper foil.

7. The preparation method according to claim 6, characterized in that: After the roughening treatment is completed, the surface is subjected to an anti-oxidation treatment.

8. Use of the double-layer copper foil according to any one of claims 1 to 4 in the preparation of copper-clad laminates.

9. The use according to claim 8, characterized in that: The stacking structure of the copper clad laminate is steel plate-backing foil-copper foil-prepreg-double-layer copper foil-prepreg-copper foil-backing foil-steel plate.

Citation Information

Patent Citations

  • Composite metal foil and manufacturing method thereof and printed wiring board

    CN101827495A

  • Composite metal foil, composite metal foil with carrier, metal-clad laminate obtained using said composite metal foil or said composite metal foil with carrier, and printed wiring board

    CN105813839A

  • Production process of double-layer composite electrolytic copper foil

    CN109267110A

  • Ultrathin strippable composite copper foil and preparation method thereof

    CN112795964A

  • Ultrathin copper foil attached to carrier foil, copper clad laminate and printed circuit board applied with same

    KR1020140023744A